Perancangan Strategi Digital Marketing untuk Meningkatkan Konsumen pada Home Industry Batik Nurari - Agrienta Bellanov; Lilis Nurhayati (Universitas Sarjanawiyata Tamansiswa, 2026)
The batik industry is a creative sector that contributes significantly to Indonesia’s economy through job creation and cultural preservation. Home Industry Batik Nurari, established in 2000 in Sidoarjo, produces various batik products, including hand-drawn batik fabrics, batik dresses, and uniforms. In response to digital transformation, Batik Nurari has utilized online marketplaces such as Shopee and Tokopedia since 2018. However, its online sales performance remains relatively low compared to similar competitors, mainly due to limited account activity, underutilization of marketplace features, and the absence of a structured digital marketing strategy. This study aims to design a systematic digital marketing strategy for a batik home industry with passive marketplace performance using the SOSTAC framework supported by quantitative SWOT analysis. The scientific contribution of this research lies in the contextual application of the SOSTAC model to a small-scale batik home industry with limited digital resources, a context that has received limited attention in previous studies. The results indicate that internal factors (strengths and weaknesses) achieve a total score of 3.30, while external factors (opportunities and threats) obtain a higher score of 3.80, demonstrating the dominant influence of external conditions on business performance. These findings suggest that digital marketing strategies should prioritize leveraging external market opportunities to enhance competitiveness and business sustainability.